VD_FINDINFO Décision / 2017 / 209 vom 20. März 2017 - VD Tribunal cantonal (2017)
DÉFENSE D'OFFICE, MANDAT, RÉVOCATIONEN GÉNÉRAL, DÉCISION D'IRRECEVABILITÉ | 38 LEP, 134 al. 2 CPP (CH), 393 al. 1 let. b CPP (CH)